Instruments for Assessing the Risk of Children and Juveniles for Conflict with the Law - Hrnčić, Jasna; Žegarac, Nevenka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
Three instruments for the assessment of the risk of children and juveniles for conflict with the law are presented in the paper. Current research on the risk factors for antisocial behaviour was briefly reviewed as a basis for creating the first instrument, Scale for Assessment of the Risk of Children and Juveniles for Conflict with the Law (Hrncic, Zegarac, Dzamonja Ignjatovic). The Scale includes nine categories: General Characteristics of the Child/Juvenile; Breaking the Rules, Hyperactivity and Aggressiveness of the Child/Juvenile; Antisocial Behaviour of the Child/Juvenile; Substance Abuse of the Child/Juvenile; Relationship of the Parent/Guardian to the Child; Characteristics of Family Members; Characteristics of Peer Group; Stressors, and Social Environment. The second instrument is the Scale of Antisocial Behaviour Chronicity Indicators (Hrncic, Zegarac), which provides a basis for the assessment of four indicators of the chronicity or pervasiveness of conflict with the law of children and adolescents: duration, frequency, seriousness and variety of antisocial behaviour. Finally, the Parental Monitoring Questionnaire was presented (Hrncic), designed for the assessment of the efficiency of parental supervision of the child.